Endophytic Fungi in Cabbage Roots: Diversity and Antagonistic effects on Rhizoctonia solani - Noor Istifadah; Sri Ageng Fitria (Biota, 2024)
Root endophytic fungi that living inside the plant roots without causing any symptom, basically is part of microorganisms in the rhizosphere or soil. Considering that, the objective of this study was to examine the effect of growth media on the occurrence and variabilities of culturable endophytic fungi in cabbage roots. The growth media examined were soil from pine forest, rhizosphere of cogon grass and elephant grass, inceptisol soil mixed with goat manure, compost or vermicompost (1:1, v/v). Fungal isolates obtained were examined their effect on the growth of cabbage seedlings and their abilities to inhibit the growth of fungal pathogen Rhizoctonia solani in vitro. The results showed that the growth media influenced the colonization and variabilities of fungal endophytes isolated from cabbage roots. The media supporting better colonization and variabilities of fungal endophytes was soil mixed with goat manure (1:1, v/v). Among 12 isolates obtained, three isolates (PK-2, PK-4 and PK-5 isolates) tended to improve the growth of cabbage seedlings. There were also three isolates (PK-1, PK-2 and TH-1) inhibited the growth of R. solani in vitro by 56.7% -64.7%.